2021
DOI: 10.1111/jrh.12606
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of cancer prevention and control resources from stakeholders in rural southern Illinois

Abstract: Purpose Rural residents have a higher cancer burden than urban residents, which is likely related to multiple socioecological factors. This study sought to investigate the perspectives of a diverse set of rural stakeholders regarding access to cancer prevention and control resources in rural southern Illinois. Methods Stakeholders were recruited from counties in southern Illinois and included residents (cancer survivors or caregivers), leaders of community‐based organizations with health‐related missions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Our participants identified several barriers that can be generally classified according to the categories established by the American College of Surgeons Commission on Cancer: patient‐, provider‐, and health system‐based barriers 41,42 . Our findings are congruent with previous studies that identified patient‐level barriers among rural residents, including finances (treatment cost and insurance coverage), transportation, and lack of social support 43 . Finances are a well‐known barrier to cancer care.…”
Section: Discussionsupporting
confidence: 91%
“…Our participants identified several barriers that can be generally classified according to the categories established by the American College of Surgeons Commission on Cancer: patient‐, provider‐, and health system‐based barriers 41,42 . Our findings are congruent with previous studies that identified patient‐level barriers among rural residents, including finances (treatment cost and insurance coverage), transportation, and lack of social support 43 . Finances are a well‐known barrier to cancer care.…”
Section: Discussionsupporting
confidence: 91%
“…Further, as Sangaramoorthy has shown in relation to immigrants in the U.S., the “precarity that characterizes rural health systems is intensified for growing communities of immigrants, who must constantly contend with the broader logics of exclusion that are at the heart of health-care and immigration reform, while also seeking care” [ 36 ]. The implications of historical and current day policies on households and on health are evident in the rural cancer research in the U.S., and are particularly pressing for Black, Latino, and Native residents of rural areas [ 2 , 41 ]. Distance to specialists and the shuttering of rural hospitals has impacted rural care seeking.…”
Section: Toward An Hhph Approach To Us Rural Cancer Disparities Researchmentioning
confidence: 99%
“…The above case, despite being from Zambia, touches on issues that run throughout rural cancer disparities research in the U.S. including distance and transportation to specialty care [ 1 , 2 , 3 ], late diagnosis and treatment [ 2 , 4 ], financial strain [ 2 , 5 ], family caregiving [ 6 , 7 ], and time spent in or adjacent to an urban hospital (e.g., in Hope Lodge or other lodging for cancer patients and caregivers) [ 8 ]. These issues are becoming even more pressing in the U.S. as rural hospital closures reach record highs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings also support that supportive care needs education and programming which addresses the structural inequalities affecting rural cancer patients and their families are needed [ 45 ]. In the absence of trusted and reliable cancer education resources, rural residents may use less reliable information sources including the internet, social media, tobacco companies, or ill-informed friends and family [ 28 , 46 ]. In an investigation testing the feasibility of a program that provides a survivorship care plan with enhanced patient education resources compared to a standard survivorship care plan, participants with the enhanced survivorship care plan reported improvements in multiple supportive care needs including emotional support, physical well-being, and nutrition [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to Structural Urbanism, rural cancer patients experience reduced access to resources (e.g., financial counselors, mental health professionals) that could resolve unmet supportive care needs (e.g., financial hardship, anxiety related to cancer) than their urban counterparts [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. To access these services, rural residents often have to travel to distal urban centers, potentially bearing additional financial, social, and physical burdens to access these services [ 5 , 28 ]. This is unfortunate, as secondary supportive care services are available before, during, and after active treatment to minimize long-term unmet supportive care needs.…”
Section: Introductionmentioning
confidence: 99%